2010
DOI: 10.1007/s00068-010-0002-4
|View full text |Cite
|
Sign up to set email alerts
|

Emergency decompressive craniectomy for trauma patients with Glasgow Coma Scale of 3 and bilateral fixed dilated pupils

Abstract: Despite control of ICP following emergency decompressive craniectomy in patients with severe TBI, GCS of 3, and BFDP, this did not change the dismal outcome of these patients; on the contrary, it may increase the suffering for patients and their families and add unnecessary medical burden. We propose that these patients have irreversible severe brain insult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Indeed, amongst others, WSES and EAST emit multiple recommendations on the non‐operative management of thoracoabdominal injuries 6,7 . The decrease observed in surgical intensity for neurotrauma during the study period may be explained by lower propensity to perform decompressive craniotomies due to controversial results from recent randomised controlled trials 10,44‐47 and recommendations emitted by the Brain Injury Foundation and Choosing Wisely 10,48 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, amongst others, WSES and EAST emit multiple recommendations on the non‐operative management of thoracoabdominal injuries 6,7 . The decrease observed in surgical intensity for neurotrauma during the study period may be explained by lower propensity to perform decompressive craniotomies due to controversial results from recent randomised controlled trials 10,44‐47 and recommendations emitted by the Brain Injury Foundation and Choosing Wisely 10,48 …”
Section: Discussionmentioning
confidence: 99%
“…At 6 months, patients were assessed and then deemed to have either a favourable (moderate disability or good recovery) or unfavourable (death, persistent vegetative state or severe disability) outcome. Patients in the DC group had 42% favourable outcomes (58% unfavourable) compared to Kirby: Decompressive craniectomy in the emergency setting Australasian Journal of Paramedicine: 2017;14 (1) 45% in the CR group (55% unfavourable). The overall results were not significant and the authors concluded that the rate of unfavourable outcomes in DC was high as patients with more severe TBIs were in the DC group; once injury severity was accounted for the outcomes are quite similar (17).…”
Section: Decompressive Craniectomy Versus Craniotomymentioning
confidence: 95%
“…Jamous et al argued that DC in these patients did not only prove unsuccessful, but prolonged the suffering of the patients and affected families. The authors of the study decided the 100% mortality rate was most likely due to the level of brain injury and these patients likely had no chance of survival regardless of treatment (1). These results should lead to further discussion regarding the exclusion of patients with a GCS score of 3.…”
Section: Indications and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent basic science and clinical research has advanced the treatment of spinal cord injury (Esposito et al, 2011;Ha et al, 2011). Different methods have been used to treat patients with spinal cord injury and have achieved some effect (Lemcke et al, 2010;Jamous et al, 2010). However, treatments remain unsatisfactory, partially because the mechanisms of ASCI remain unclear, thereby preventing the development of improved therapeutics.…”
Section: Introductionmentioning
confidence: 99%